2022
DOI: 10.1038/s41598-022-24240-3
|View full text |Cite
|
Sign up to set email alerts
|

Probable COVID-19 infection is associated with subsequent poorer mental health and greater loneliness in the UK COVID-19 Mental Health and Wellbeing study

Abstract: The COVID-19 pandemic has been associated with psychological distress. In addition to physical effects including fatigue and cognitive impairment, contracting COVID-19 itself may also be related to subsequent negative mental health outcomes. The present study reports data from a longitudinal, national survey of the UK adult population investigating whether contracting suspected or confirmed COVID-19 at the early stages of the pandemic (March–May 2020) was associated with poorer mental health outcomes in May/Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Unlike the study of Wilding et al ( 95 ), Razali et al ( 63 ), and Hecker et al ( 96 ) studies, which focused on the direct causal relationship between COVID-19 and residents’ mental health, our research innovatively and empirically confirms the promotion role of the RCC in improving residents’ mental health. Firstly, the RCC has canceled the home restriction and isolation control policy ( 97 , 98 ), so that residents can have free activities and seek the best comfortable environment.…”
Section: Discussionsupporting
confidence: 45%
“…Unlike the study of Wilding et al ( 95 ), Razali et al ( 63 ), and Hecker et al ( 96 ) studies, which focused on the direct causal relationship between COVID-19 and residents’ mental health, our research innovatively and empirically confirms the promotion role of the RCC in improving residents’ mental health. Firstly, the RCC has canceled the home restriction and isolation control policy ( 97 , 98 ), so that residents can have free activities and seek the best comfortable environment.…”
Section: Discussionsupporting
confidence: 45%
“…During the COVID-19 period, the overall number and level of mental health problems are increasing rapidly compared to before around the world. A study aiming to investigate alternation in using mental health services resources in the UK, and how these changes' influences on the general mental health during the COVID-19 pandemic, shows the increased risk of mental illness will lead to the need for innovative or more mental health support for about twenty percent of the population in the UK [2]. Not only in the UK, but also in other countries around the world.…”
Section: Main Groups Suffered From Mental Health During the Covid-19 ...mentioning
confidence: 99%
“…Another main group that suffers from high levels of stress is the nurses and other medical staff. As Sarah Wilding and her colleagues' paper shows, the increasing of patients with mental health problems has a direct correlation with COVID-19, "individuals who had contracted probable COVID-19 had poorer outcomes on the measures" [2]. The rapid increase of patients waiting for psychological treatment added more stress and anxiety to the nurses and medical staff; the data shows that there's at least one in every five who report symptoms like feeling anxious, depressed and stressed [5].…”
Section: Main Groups Suffered From Mental Health During the Covid-19 ...mentioning
confidence: 99%
“…In addition, some of those affected also suffer from psychological symptoms such as anxiety, depression or sleep disorders 9 , 10 . A recent longitudinal study from the UK showed that anxiety disorders and depression are more common in COVID-19 patients than in participants without COVID-19 11 . Furthermore, an increased risk of developing mental illness after SARS-CoV-2 infection was shown 12 , and another study found that 64% of patients with unexplained long-term neurological symptoms met the criteria for the presence of somatisation disorder 13 .…”
Section: Introductionmentioning
confidence: 99%